Coherence in hybrid texts: The case of the Patient Information Leaflet genre - Hill-Madsen, Aage (HERMES - Journal of Language and Communication in Business, 2019)
This article investigates the degree of coherence in a particular type of hybrid text, viz. the Patient Information Leaflet, which is a lay-oriented genre fusing original and derived textual elements. Having their source in the specialized genre named Summary of Product Characteristics, derived segments undergo various kinds and degrees of registerial simplification in the transfer to the Patient Information Leaflet. Given this complex textual genesis, the aim of the article is to investigate the nature and degree of coherence in the Patient Information Leaflet genre, and, more specifically, to investigate the degree of integration between derived and non-derived elements. Following Halliday/Hasan’s (1976) definition of the coherence concept, the article examines the genre’s contextual coherence in the form of registerial consistency and its text-internal coherence in the form of cohesiveness. For the investigation of cohesiveness, the analytical framework known as Cohesive Harmony Analysis (Hasan 1984, 1985) has been applied to a sample text from the genre, and likewise to a parallel lay-oriented, but non-hybrid text from the health column of a British quality newspaper, which serves as a control. While the investigation confirms already well-known problems with registerial consistency in the Patient Information Leaflet genre, the analytical results reflect a high degree of cohesiveness, and one that is even markedly higher than that of the non-hybrid control text. Further, the results reflect a high level of integration between derived and non-derived segments in the Patient Information Leaflet.